Answer:
b = -6
Step-by-step explanation:
Apply the exponent rule that
In this case, ![\frac{1}{y^{24}} = y^{-24}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7By%5E%7B24%7D%7D%20%20%3D%20y%5E%7B-24%7D)
Set that equal to
:
![(y^{b})^{4} = y^{-24}](https://tex.z-dn.net/?f=%28y%5E%7Bb%7D%29%5E%7B4%7D%20%3D%20y%5E%7B-24%7D)
Apply the exponent rule that
so now you get:
![y^{4b} = y^{-24}](https://tex.z-dn.net/?f=y%5E%7B4b%7D%20%3D%20y%5E%7B-24%7D)
Since the base is y for both sides of the equation, just set the exponents equal to each other and solve for b.
4b = -24
divide each side by 4 to get:
b = -6
Answer:
No Solutions.
Step-by-step explanation:
I will solve your system by substitution.
3y−3=3x; −3x+3y=−57
Step: Solve 3y−3=3x for y:
3y−3+3=3x+3 (Add 3 to both sides)
3y=3x+3
(3y/3=3x+3)/3
(Divide both sides by 3)
y=x+1
Step: Substitute x+1 for y in −3x+3y=−57:
−3x+3y=−57
−3x+3(x+1)=−57
3=−57 (Simplify both sides of the equation)
3+(−3)=−57+(−3) (Add -3 to both sides)
0=−60
Answer: E, A, D, C, B
Step-by-step explanation:
First, we need to get y alone. So we will add 7 to the side of the equation that has the 4y in it.
So the first one will be.
<em><u>Add 7 to both sides of the equation.</u></em>
Now the second one is
<em><u>4y = 25 + 7 </u></em>Because what you do to one side of the equation, you do to the other. So we add 7 to 25.
Then the 3rd one will be <u><em>4y = 32 </em></u>because 25+7 is equal to 32. But we still have that 4y on the other side of the equation. So the next equation is 4y = 32.
The second to last step is <em><u>Divide both sides by 4 </u></em>because thats
how you isolate y. So once you divide both sides by 4. You will get 8. Leading you into the next and final step.
<em><u>Y = 8</u></em>
And thats how you do it!
Answer:
12
Step-by-step explanation:
Answer:Surface
Step-by-step explanation: